CNN pincer ruthenium complexes for efficient transfer hydrogenation of biomass-derived carbonyl compounds. Issue 2 (13th December 2019) - Figliolia, Rosario; Cavigli, Paolo; Comuzzi, Clara; Del Zotto, Alessandro; Lovison, Denise; Strazzolini, Paolo; Susmel, Sabina; Zuccaccia, Daniele; Ballico, Maurizio; Baratta, Walter
Abstract : Robust and easily accessible CNN OMe pincer ruthenium complexes show unprecedented selectivity and productivity in the TH of lignocellulose-derived carbonyl compounds with 2-propanol. Abstract : The ligand HCNN OMe (6-(4-methoxyphenyl)-2-aminomethylpyridine) is easily prepared from the commercially available 6-(4-methoxyphenyl)pyridine-2-carbaldehyde by the reaction of hydroxylamine and hydrogenation (H2, 1 atm) with Pd/C. The pincer complexes cis -[RuCl(CNN OMe )(PPh3 )2 ] (1 ) and [RuCl(CNN OMe )(PP)] (PP = dppb, 2 ; and dppf, 3 ) are synthesized from [RuCl2 (PPh3 )3 ], HCNN OMe and PP (for 2 and 3 ) in 2-propanol with NEt3 at reflux and are isolated in 85–93% yield. Carbonylation of 1 (CO, 1 atm) gives [RuCl(CNN OMe )(CO)(PPh3 )] (4 ) (79% yield) which cleanly reacts with Na[BAr f 4 ] and PCy3, affording the cationic trans -[Ru(CNN OMe )(CO)(PCy3 )(PPh3 )][BAr f 4 ] (5 ) (92% yield). These robust pincer complexes display remarkably high catalytic activity in the transfer hydrogenation (TH) of lignocellulosic biomass carbonyl compounds, using 2-propanol at reflux in a basic medium (NaOiPr or K2 CO3 ). Thus, furfural, 5-(hydroxymethyl)furfural and Cyrene are reduced to the corresponding alcohols with 2 and 3, at S/C in the range of 10 000–100 000, within minutes or hours (TOF up to 1 500 000 h −1 ). The monocarbonyl complex 5 was found to be extremely active in the TH of cinnamaldehyde, vanillin derivatives and ethyl levulinate at S/C in the range of 10 000–50 000. Vanillyl alcohol is also obtained by the TH of vanillin with 5 (S/C = 500) in 2-propanol in the presence of K2 CO3 .